Structural Characterization of Peptides From Huangjiu and Their Regulation of Hepatic Steatosis and Gut Microbiota Dysbiosis in Hyperlipidemia Mice - Shi, Ying; Feng, Ruixue; Mao, Jieqi; Liu, Shuangping; Zhou, Zhilei; Ji, Zhongwei; Chen, Shuguang; Mao, Jian (Frontiers in Pharmacology, 2021)
Hyperlipidemia is a chronic disorder that is difficult to cure and usually treated with long-term lipid-reducing drugs. Recent trends have led to the use of diet therapies or food-derived strategies in the treatment of such long-term diseases. The Chinese rice wine (huangjiu) contains a wide range of bioactive peptides that are produced during the multi-species fermentation process. To clarify the regulation effects of lipid metabolism and gut microbiota by huangjiu bioactive peptides, three huangjiu peptides were isolated, purified and characterized by hyper-filtration, macroporous resin, gel filtration separation and structural identification. Meanwhile, a mouse model of high-fat diet-induced hyperlipidemia was established to study the effects of huangjiu peptides on serum biomarker, hepatic metabolism and gut microbiota dysbiosis. Experimental results showed that huangjiu peptides T1 and T2 (HpT1, HpT2) treatment alleviated the increase in serum total cholesterol, triglyceride, low-density lipoprotein cholesterol levels and aberrant hepatic lipid accumulation in the high-fat diet-induced hyperlipidemia mice. Furthermore, HpT2 and HpT1 restored the α-diversity and structure of gut microbial community after hyperlipidemia-induced microbiota disturbance compared with simvastatin and HpT3. The administration of HpT2 and HpT1 regulated the microbiota-mediated gut ecology through alterations of characteristic taxa including Lactobacillus, Ileibacterium, Faecalibaculum and Alloprevotella by linear discriminant analysis effect size analysis. Collectively, our results offer new insights into the abilities of food-derived peptides on alleviation of high-fat diet-induced hyperlipidemia, hepatic steatosis and gut dysbiosis in mice.